Pengaruh Program Reward dan Recognition, serta Kepuasan Kerja terhadap Kinerja Karyawan Bagian Operasional di Bca Kcu Veteran Surabaya - Kridho Hery Gunawan; Renatha Dewi Puspita Sari (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
A research team at BCA KCU Veterans Company in Surabaya conducted a study to determine how job satisfaction and their participation in recognition and reward programs affect their performance at work. By sending a survey to 66 workers in the business sector, this study applied quantitative survey stages. Multiple linear regression evaluation was performed on the collected data. Workplace performance was the dependent variable, while factors such as salary, appreciation, and overall job satisfaction were the independent variables. The findings revealed that all three independent variables simultaneously impact employee productivity. Salary, benefits, bonuses, and incentives serve to motivate employees to work harder. Employees feel psychologically motivated when their efforts and achievements are recognized through awards. Job satisfaction makes people more dedicated and efficient. The coefficient of determination (R²) of 0.629 indicates that factors other than recognition, appreciation, and job satisfaction influence the remaining variation in employee performance, accounting for 62.9%. To motivate employees to perform at their best, this study highlights the importance of implementing efficient recognition and appreciation programs and creating a work environment that supports job satisfaction.